Validation of ratings on the six-item Positive and Negative Syndrome Scale obtained via the Simplified Negative and Positive Symptoms Interview among outpatients with schizophrenia. (November 2022) - Nielsen, Cecilie Marie; Kølbæk, Pernille; Dines, David; Pedersen, Martin Locht; Danielsen, Andreas Aalkjær; Holmgård, Camilla; Wissing, Sanne; Esbøl, Anne-Mette; Fuglsang, Nina Friis Bak; Nguyen, Tuan Dang; Mors, Ole; Opler, Mark; et al.
Background: The six-item Positive and Negative Syndrome Scale (PANSS-6) is a measure of the severity of core symptoms of schizophrenia, which can be administered via the brief Simplified Negative and Positive Symptoms Interview (SNAPSI). A recent study has confirmed the validity of PANSS-6 ratings as derived by SNAPSI (PANSS-6SNAPSI ) among inpatients with schizophrenia. Aims: We aimed to test the validity of PANSS-6SNAPSI among outpatients with schizophrenia using PANSS-6 ratings extracted from the 30-item PANSS-30 as derived by the Structured Clinical Interview for the Positive and Negative Syndrome Scale (PANSS-6SCI-PANSS ) as a gold standard reference. Methods: PANSS-6SNAPSI and PANSS-6SCI-PANSS ratings were obtained at two time points by independent raters with established inter-rater reliability. Agreement between PANSS-6SNAPSI and PANSS-6SCI-PANSS ratings was estimated via intra-class coefficients (ICCs) and responsiveness over time was quantified using Spearman's rank correlation coefficients. Post hoc "leave-one-out" analyses were carried out, in which each rater in turn was excluded from the ICC calculations. Results: Seventy-three outpatients with schizophrenia participated in the study (mean age: 38.3 years; 56% males). The ICC for PANSS-6SNAPSI versus PANSS-6SCI-PANSS was 0.67 [95%CI = 0.56–0.76] and the Spearman's rank correlation coefficient for responsiveness was 0.40 ( p  = 0.004). When data from a specific outlying rater were excluded, the ICC for PANSS-6SNAPSI versus PANSS-6SCI-PANSS was 0.75 [95% CI = 0.63–0.83] and the Spearman's rank correlation coefficient for responsiveness was 0.55 ( p  = 0.018). Conclusions: We found PANSS-6SNAPSI ratings to have acceptable clinical validity, suggesting that PANSS-6SNAPSI can be used for both inpatients and outpatients with schizophrenia.